Compensation orthodontic treatment of an adult patient with bilateral cleft lip and palate clip. Case Report - Madrid, Otto; Jaramillo, Isabel-Cristina; Barhoum, Habib (Revista Estomatología, 2015)
Clinical case of a 28 year old patient with bilateral cleft lip palate, who was treated during a period of 5 years and 4 months, at the University of Valle postgraduate orthodontic’s clinic of lip and palate, is presented. The patient had undershot jaw, severe mandibular macrognatismo, molar malocclusionclass I and class II right and left, accompanied by severe recumbent and mild retrusión of upper incisors and lower and, multiple malposition and impaction tooth 12. A non - surgical orthodontic plan compensation was developed and accompanied by an initial mandibular treatment, orthopedic expansion and corrective orthodontic treatment, using fixed appliances such as standard braces slot 0.22x0.028 inches, extractions of lower first premolars, typing canines as lateral incisors as well as rehabilitation of the upper front teeth. Satisfactory results were obtained in terms of aesthetic and functional occlusion. Key words: Cleft lip, cleft palate, orthodontic treatment of compensation, bilateral cleft lip and palate.